Contemporary treatment of right ventricular failure - Bibhuti B. Das, MD; Shashi Raj, MD, FAAP, FACC (JHLT Open)
Right ventricular failure (RVF) is a clinical syndrome resulting from structural and functional changes in the right ventricle (RV), leading to inadequate blood flow to the pulmonary circulation and elevated systemic venous pressures. Factors modulating RV function include afterload, preload, contractility, and interventricular dependency. The pathophysiology of RVF involves complex interactions, such as maladaptive hypertrophy, metabolic reprogramming, inflammation, fibrosis, apoptosis, and endothelial dysfunction. Therapeutic strategies are limited for RVF, as basic and clinical research has historically focused mainly on the left ventricle. Novel pharmacological interventions targeting metabolism, calcium homeostasis, oxidative stress, extracellular matrix remodeling, endothelial function, and inflammation are needed to address RVF effectively. This review explores the etiology, mechanisms, and pathophysiology of RVF, drugs directly targeting the RV myocardium, the intricate biological processes between RV and pulmonary vascular remodeling, surgical and device therapies, and future perspectives on managing RVF.